2015
DOI: 10.3329/bjsir.v49i4.22622
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of Spirulina platensis (Nordst) Geitler, in cabbage extract and antibacterial activities in different culture media

Abstract: Growth response of Spirulina platensis (Nordst) Geitler in cabbage skin extract media and their antibacterial activities were studied. Five different concentrations e.g. 10 , 8 ,6 , 4 and 2 gm/L of cabbage skin extract media and one BD1 (control) medium were used in this experiment. Highest optical density was observed in 10 gm/L cabbage skin extract medium (0.35) followed by BD1 medium (0.30) after fifteen days of culture. Antibacterial activity of S. platensis was studied. Only freeze dried S. platensis powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…These wastes were made into a cabbage extract medium that promoted growth of the microalgae after 15 days, with the highest concentration (10 g L −1 ) producing maximum spirulina biomass of 550 g L −1 (Akhtar et al . 2014). The extracts were an excellent source of vitamins, amino acids and other nutrients, especially because NaCl, NaHCO 3 and urea were added.…”
Section: Alternatives To Zarrouk’s Medium: Research Trendsmentioning
confidence: 99%
See 4 more Smart Citations
“…These wastes were made into a cabbage extract medium that promoted growth of the microalgae after 15 days, with the highest concentration (10 g L −1 ) producing maximum spirulina biomass of 550 g L −1 (Akhtar et al . 2014). The extracts were an excellent source of vitamins, amino acids and other nutrients, especially because NaCl, NaHCO 3 and urea were added.…”
Section: Alternatives To Zarrouk’s Medium: Research Trendsmentioning
confidence: 99%
“…The anti‐bacterial properties of the spirulina culture in different media were also assessed by Akhtar et al . (2014) and reported that only freeze‐dried S. platensis powder extracts exhibited anti‐bacterial potency against Streptococcus pneumoniae , Bacillus subtilis , Shigella dysenteriae and Sarcina lutea . Cabbage skin extracts medium was also compared to the Zarrouk’s medium as control and Bangladesh medium 1 (BD1).…”
Section: Alternatives To Zarrouk’s Medium: Research Trendsmentioning
confidence: 99%
See 3 more Smart Citations